Neem - a natural insecticide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The insect-repellent qualities of oil extracted from the fruit of the neem tree, and of cake from its residue after pressing, are being studied at the International Rice Research Institute (IRRI). This is part of a program me to develop biological...